Metal Artifact Suppression in Dental Cone Beam Computed Tomography Images Using Image Processing Techniques - Johari, Masoumeh (J Med Signals Sens, 2018)
BACKGROUND: Dental cone beam computed tomography (CBCT) images suffer from severe metal artifacts. These artifacts degrade the quality of acquired image and in some cases make it unsuitable to use. Streaking artifacts and cavities around teeth are the main reason of degradation. METHODS: In this article, we have proposed a new artifact reduction algorithm which has three parallel components. The first component extracts teeth based on the modeling of image histogram with a Gaussian mixture model. Striking artifact reduction component reduces artifacts using converting image into the polar domain and applying morphological filtering. The third component fills cavities through a simple but effective morphological filtering operation. RESULTS: Finally, results of these three components are combined into a fusion step to create a visually good image which is more compatible to human visual system. CONCLUSIONS: Results show that the proposed algorithm reduces artifacts of dental CBCT images and produces clean images.